A new species of Gymnogeophagus from the río Negro and río Tacuarí basins, Uruguay (Teleostei: Perciformes) - Iván González-Bergonzoni; Marcelo Loureiro; Sebastián Oviedo (Neotropical Ichthyology)
The new cichlid species Gymnogeophagus tiraparae is described from the río Negro and río Tacuarí basins (Uruguay). The new species is distinguished from other Gymnogeophagus species by the unique presence of the following characters: adipose hump on head deeper than the dorsal-fin upper border, adipose hump with anterior profile vertical, extending from the upper lip to the dorsal-fin origin, absence of transversal bands on body; two horizontal series of moderately elongated light blue dots between dorsal fin spines, and a series of light blue stripes between soft rays, sometimes merged with the second series of elongated dots, always with a red ground color between series of dots, and caudal fin with dots vertically aligned on its distal border. According to these characters and a recent molecular phylogenetic analysis, the new species is closely related to G. gymnogenys.